Home infusion services in Saudi Arabia: Where are we standing? - Abdullah A. Alhifany; Abdulaziz T. Ghilais; Jawad A. Jammal; Faisal M. Alfaifi; Sarah M. Khayyat; Abdulmalik S. Alotaibi; Mohammed Alessa; Thamer A. Almangour (Elsevier, 2023)
Diseases management has reached the highest level of complexity and cost in history, worldwide, and in Saudi Arabia in particular, which led to prolonged, unnecessary hospital stays. There have been many recent innovative measures to reduce these issues. One is to provide home infusion services. Hence, this narrative review emphasizes the expected benefits and challenges of such services and the applicability of their implementation in Saudi Arabia. A literature search was conducted via PubMed database, involving all published studies from inception until March 24th, 2023. Many studies showed positive impacts of home infusion on reducing the length of hospital stays, increasing cost-saving, and leading to high patient satisfaction.